Subclinical Ultrasonographic Abnormalities of the Suspensory Ligament Branches Are Common in Elite Showjumping Warmblood Horses - Read, Rachel Mercedes; Boys-Smith, Sarah; Bathe, Andrew Perry (Frontiers in Veterinary Science, 2020)
Background: There is limited information concerning the ultrasonographic appearance of suspensory ligament branches (SLB) in sports horses. Publications exist on clinical injuries that lead to loss of training days and retirement, but not on the appearance of SLBs in normal high level showjumping Warmbloods. Objectives: To demonstrate the prevalence of subclinical SLB abnormalities in regularly competing high-level showjumpers; to grade each branch 0-3; compare forelimb versus hindlimb and medial versus lateral SLBs; subjectively assess periligamentous fibrosis; measure cross sectional area (CSA) and to gather competition follow-up data. Study design: Prospective cross-sectional study using ultrasonograms. Methods: 60 elite showjumping Warmbloods without recent history or clinical signs of SLB desmopathy were examined ultrasonographically. Eight static images of each SLB were acquired in transverse and longitudinal sections, anonymised and stored. Images were then assessed and graded by 2 experienced blinded clinicians based on a published ordinal scale (grade 0-3). A branch score was assigned based on the most severe grade of any image slice in each branch series. SLB cross-sectional area measurement was obtained from each SLB using the transverse image proximal to insertion. Results: The frequency of grade 2 (moderate) ultrasonographic abnormalities was high. Combined data showed a prevalence of 58% (554/960) grade 2 SLBs. Interobserver agreement was good (kappa=0.65). Periligamentous fibrosis was over represented in hindlimbs (64%). Combined observer data showed there was no statistical difference in branch scores based on limb or laterality. Follow-up over 12 months revealed only 2 horses were excluded from competition due to SLB injury. Main Limitations: Sample size was small. Images were obtained in static mode, limbs were not clipped of hair, lameness evaluation was under FEI veterinary inspection and not performed by the authors and follow-up evaluation was from FEI competition records and communication only, and was limited to 1 year. Conclusions: Regularly competing elite showjumping Warmbloods have a high prevalence of subclinical SLB ultrasongraphic abnormalities, which may not contribute to causing lameness, poor-performance or be viewed entirely negatively at prepurchase examination. Judicious interpretation of moderate severity SLB abnormalities is advised due the low incidence of clinical injury demonstrated during the 1 year follow-up.